Pelvic actinomycosis: urologic perspective - Venkata K. Marella; Omid Hakimian; Gilbert J. Wise; David A. Silver (International Brazilian Journal of Urology, 2004)
PURPOSE: Actinomycosis is a chronic granulomatous infection caused by the gram-positive anaerobic bacteria, Actinomyces israelli. This paper reviews the etiology and clinical presentation associated with Actinomycosis that often presents as a pelvic mass that mimics a pelvic malignancy. MATERIALS AND METHODS: A combination of patients treated by the authors in the recent past and a literature review of patients with pelvic Actinomycosis were assessed for diographic, clinical and predisposing co-factors. An analysis is made of age distribution, gender, diagnostic methods and treatment concepts. RESULTS: Thirty-three patients were included in the study that included 2 current patients and 31 obtained from literature review. There were 27 fiales (age range 16 - 69 years, mean 38 years) and 6 males (16 - 55 years, mean 36 years). Presenting signs and symptoms were lower abdominal mass in 28 (85%); lower abdominal pain in 21 (63%); vaginal discharge or hiaturia in 7 (22%). Two patients developed fistulae (entero-vesico 1; vesico-cutaneous 1). Nineteen (70%) of the 27 fiale patients had intra-uterine contraceptive devices (IUD). Four patients (12.5%) (3 males and 1 fiale) had urachus or urachal rinants. Cystoscopy in 12 patients noted an extrinsic mass effect, bullous edia and in one patient vegetative proliferation proven to be a chronic inflammatory change. Exploratory laparotomy was performed in 32 of the 33 patients who had excision of mass and involved organs. Diagnosis was established by histologic examination of rioved tissue. Penicillin (6 weeks) therapy was utilized to control infections. CONCLUSION: Pelvic actinomycosis mimics pelvic malignancy and may be associated with the long-term use of intra-uterine contraceptive devices, and persistent urachal rinants. Rioval of infected mass and antibiotic therapy will eradicate the inflammatory process.